Peran Konformitas dan Kontrol Diri terhadap Adiksi Game Online pada Remaja Awal - Ridwan Abdillah; Agoes Dariyo (Lembaga Yasin AlSys, 2026)
The development of digital technology has made it easier for early adolescents to access various entertainment platforms, including online games, at a developmental stage in which a strong tendency to conform to peers and unstable self-control increase vulnerability to online game addiction. This study aimed to examine the roles of conformity and self-control in online game addiction among early adolescents in West Jakarta. A quantitative approach with a causal design was employed, involving 265 early adolescents aged 12–15 years selected using a simple random sampling technique. The research instruments consisted of the Self-Control Scale (SCS) Brief Version, a Conformity Scale, and the Game Addiction Scale (GAS), all of which had undergone adaptation, validity, and reliability testing. Data were analyzed using multiple linear regression. The results showed that conformity had a positive and significant effect on online game addiction, whereas self-control had a negative and significant effect. Simultaneously, conformity and self-control contributed 35.1% to online game addiction (R² = 0.351), while the remaining 64.9% was influenced by other factors. These findings underscore the crucial roles of conformity and self-control in shaping online gaming behavior among early adolescents and provide an empirical basis for developing preventive intervention programs focused on strengthening self-control and managing peer-group influence.